2021
DOI: 10.1021/acsami.1c16087
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Gelling Dendronized Chitosans as Biomimetic Scaffolds for Corneal Tissue Engineering

Abstract: Biomimetic scaffolds with transparent, biocompatible, and in situ-forming properties are highly desirable for corneal tissue engineering, which can deeply fill corneal stromal defects with irregular shapes and support tissue regeneration. We here engineer a novel class of corneal scaffolds from oligoethylene glycol (OEG)-based dendronized chitosans (DCs), whose aqueous solutions show intriguing sol–gel transitions triggered by physiological temperature, resulting in highly transparent hydrogels. Gelling points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Amidation of high-molar-mass CS with threefold dendritic TEGs 39 afforded DCS (TEG-CS) with dendron coverage of 55%, which was determined by acid−base titration according to our previous report. 38 For comparison, dendronized chitosan (DEG-CS, dendron coverage is 58%) carrying more hydrophobic threefold dendritic DEGs and dendronized oligosaccharide of much shorter main chains (TEG-CSO, dendron coverage is 52%) with threefold dendritic TEGs were also prepared, respectively, to examine the architecture effects of DCSs on the formation and stability of the nanoparticles. Synthetic procedures of these three DCSs are shown in Scheme S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amidation of high-molar-mass CS with threefold dendritic TEGs 39 afforded DCS (TEG-CS) with dendron coverage of 55%, which was determined by acid−base titration according to our previous report. 38 For comparison, dendronized chitosan (DEG-CS, dendron coverage is 58%) carrying more hydrophobic threefold dendritic DEGs and dendronized oligosaccharide of much shorter main chains (TEG-CSO, dendron coverage is 52%) with threefold dendritic TEGs were also prepared, respectively, to examine the architecture effects of DCSs on the formation and stability of the nanoparticles. Synthetic procedures of these three DCSs are shown in Scheme S1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…38,39 These water-soluble DCSs can form not only thermoresponsive hydrogels through dynamic covalent imines as injectable stem cell carriers when carrying hydrophilic dendritic triethylene glycol (TEG) pendants but also highly transparent thermo-gelling hydrogels via dendronization with more hydrophobic dendritic diethylene glycol (DEG) pendants, which are promising as biomimetic scaffolds for corneal tissue engineering. 38 Through dendronization of chitosan oligosaccharides (CSO) with the dendritic TEGs, we reported that dendronized chitosan oligosaccharides (DCSOs) can act as intriguing templates to reduce silver ions when triggered by visible light in aqueous solutions in the absence of any external reducer, affording monodispersed and stable AgNPs with size less than 5 nm, which can simultaneously encapsulate and stabilize the formed silver nanoparticles (AgNPs) to form stable nanocomposites and exhibit promising antibacterial properties. 40 As a continuation, we report here our development of a kind of molecular-level nanoreactor based on DCSs with a longer polysaccharide mainchain and more abundant dendritic OEG pendants in individual polymers for improving the stability of nanoparticles as well as intriguing thermoresponsive properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our previous reports, we found that dendronization of polypeptides or chitosans with dendritic oligoethylene glycols (OEGs) affords biomacromolecules with characteristic LCSTtype thermoresponsive behavior. [40][41][42] The resulting polymers retained their original properties, such as enhanced α-helix conformation and satisfactory biocompatibility. Herein, through modification of gelatin with dendritic OEGs, we report the synthesis of a new type of dendronized biomacromolecule that combines the unique properties of gelatin with the thermoresponsiveness of OEG dendrons (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…We anticipated that the morphology difference originated from the different amphiphilicity of the gelatins. Through sufficient dendronization of gelatin with OEG dendrons, the pendants and the gelatin backbone may form radial amphiphilicity to enhance assembly, 40,42 leading to ordered morphologies after gelation. Because these microporous GelG1 hydrogels are able to integrate the cell adhesive ability of gelatin, they are potential biomaterials that can be used for 3D cell culture.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…Another innovative approach was described by Feng et al, who developed transparent thermogelling scaffolds using oligoethylene glycol-based dendronized chitosan [152]. Interestingly, the gel point of these systems can be easily adjusted.…”
Section: Cornea Damagementioning
confidence: 99%